1998
DOI: 10.1093/humrep/13.8.2301
|View full text |Cite
|
Sign up to set email alerts
|

Selective termination and elective reduction in twin pregnancies: 10 years experience at a single centre

Abstract: Selective termination is employed in multifetal pregnancies, in the presence of an abnormal fetus, in order to improve the prognosis of the normal fetuses. The term elective reduction is used to describe reduction in twin pregnancies for maternal medical conditions, psychological, or socioeconomic reasons. The purpose of this study was to evaluate the factors that influence outcome in such pregnancies. Eighty-two twin pregnancies underwent selective termination (n = 59) or elective reduction (n = 23) over a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
3
26
1
Order By: Relevance
“…The miscarriage rate was higher in first-trimester procedures, which may be partly explained by the higher loss rate in earlier gestations, and severe preterm delivery ( 5 33 weeks) was higher in second-trimester procedures. Similar results were reported by Yaron and colleagues in a study of 82 twin pregnancies that underwent selective termination, 31 in the first and 51 in the second trimester, the authors concluding that late procedures were associated with a higher rate of preterm delivery and lower birth weight 13 . The trend towards lower loss rates in first-trimester procedures was also confirmed by Evans and associates in a study of 345 sets of twins 23 .…”
Section: Discussionsupporting
confidence: 84%
“…The miscarriage rate was higher in first-trimester procedures, which may be partly explained by the higher loss rate in earlier gestations, and severe preterm delivery ( 5 33 weeks) was higher in second-trimester procedures. Similar results were reported by Yaron and colleagues in a study of 82 twin pregnancies that underwent selective termination, 31 in the first and 51 in the second trimester, the authors concluding that late procedures were associated with a higher rate of preterm delivery and lower birth weight 13 . The trend towards lower loss rates in first-trimester procedures was also confirmed by Evans and associates in a study of 345 sets of twins 23 .…”
Section: Discussionsupporting
confidence: 84%
“…In search of a possible explanation to the higher than expected complications rate in reduced twin pregnancies compared to singleton pregnancies, we tried to define the importance of reduction timing. We assumed that pregnancy complications will be more prevalent in pregnancies in which reduction was performed later as Yaron et al [15] and Antsaklis et al [3] both described higher rates of preterm delivery at second trimester reductions. We demonstrate a higher incidence of late abortion and premature delivery when reduction is beyond 15 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…8 Two other studies compared the risks of adverse pregnancy outcomes in twins reduced to singletons by a single and multiple operators with national databases of ongoing twins and showed similar results. 6,7 There have been multiple studies looking at the loss rates of selective reduction and multifetal pregnancy reduction in twin pregnancies. Whereas older and smaller studies showed loss rates that ranged from 4.76% to 9.09%, 8,11,12 the largest and most recent studies showed a loss rate between 2.1% and 2.5%.…”
Section: Commentmentioning
confidence: 99%
“…6,7 However, in one small retrospective study comparing 35 ongoing twin pregnancies with 32 reduced pregnancies in a single unit, the authors found no difference in outcomes between the cohorts. 8 However, this study was underpowered, given the small numbers in both the study and the control groups used.…”
mentioning
confidence: 99%